Two interpretations of Hegel: art between the social and the anthropological Due interpretazoini di Hegel: Parte tra il sociale e l’antropologico - Cruz Guerrero, Dany Erick (2023)
The philosophical-critical study of art and its insertion in Hegel’s early work highlights two ap- parently irreconcilable antagonistic critical tendencies in the interpretations that specialized critics work to understand the profound intention of the magnificent German thinker. The essay checks that specialized criticism lacks a method that facilitates the integration of art into the Hegelian system and shows how this lack impacts the emergence of the sociological-structuralist interpreta- tion and its replica, the anthropological interpretation. To help fill this gap, the essay discerns and abstracts the limits of the two controversial interpretations mentioned and takes advantage of the results obtained to demonstrate how, examined from a synergistic approach of complementarity, they contribute to bringing out the Hegelian philosophy of art, making it possible to perceive, in its fundamental terms, how art is inscribed in the Hegelian system from its beginnings as an irrevocable fundamental principle.